Rancangan Model Konseptual denganTheory of Contraints untuk Menyeimbangkan Lini Produksi dan Meningkatkan Output pada Industri Komponen Otomotif - Rachman Catur Kurniawan; Iveline Anne Marie; Nora Azmi (Universitas Mercu Buana, 2022)
Nowadays, competition among manufaktur industries is increasing rapidly. This competition causes similar industries to compete, including the automotive component industry. To win the competition, the automotive component manufaktur industry must carry out various repair methods. Improvements made include managing inventory, scheduling, delivery, quality management and eliminating waste. Based on observations, problems that often occur in the automotive component manufaktur industry are not achieving production output and unbalanced production lines so that problems such as waste and bootleneck arise. The purpose of this research is to design a model on the production line to increase production output and balance the production line. The method used to analyze and solve this problem is to design a conceptual model of Theory of Constraints (ToC). This method interprets structured and systematic stages to solve problems in the manufaktur industry. Based on the analysis, the results of this study produce a generic model that can be used in the automotive component industry. The models offered can increase production output, balance workloads and eliminate waste.